The Effect of Blended Learning Simulation on Learning Outcome - Sri Rahayu Surtiningtyas (Language, Literature and Education: Research Updates Vol. 3, 2025)
The development of aviation training grew rapidly along with the development of technology and science. Therefore, it is necessary for instructional designers to produce new instructional models to take advantage of educational research and development results. This paper presents the formative evaluation for an instructional model for Aerodrome Flight Information training development. The developed instructional model was a blending of e-briefing with face-to-face role-play simulation and debriefing. The aim of this study was to improve the effectiveness of the developed instructional model. Respondents were selected from eight students who represent low, medium, and high learning achievement students. This study employed a formative evaluation by Tessmer in 2013, with both qualitative and quantitative approaches. The respondents of the field test are 22 students of the 2016-2017 academic year. The formative evaluation consisted of expert review, one-to-one, small group, and field test. This research was carried out at the Indonesian Civil Aviation Institute. The data were collected through open-ended interviews, questionnaires, and field observations. The data analysis used descriptive statistical methods. The finding indicates that the blended learning simulation-based model increased learning outcome (+12.55); students and instructors were more satisfied when they implemented this model, is 4.47; and the model increased students’ attention level is 4.5. Based on the findings, the proposed instructional model can be implemented in this institution.